PERAN BRAND IMAGE MEMEDIASI PENGARUH KREDIBILITAS CELEBRITY ENDORSER TERHADAP PURCHASE INTENTION - Weking, Maria Margaretha Annisa Prameswari; Oktora Panasea, I Gede Nandya (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023DO - 10.24843/BSE.2025.v30.i01.p08, 2025)
The rapidly growing beverage business requires companies to offer quality beverage products through attractive promotions using celebrity endorsers to strengthen consumer memories of the product brand image so that it will attract the attention of potential consumers to have buying interest, where one of the beverage products is Good Day coffee. This study aims to explain the role of brand image as a mediator in the influence of celebrity endorser credibility on purchase intention. This research was conducted on potential customers in Denpasar City who have never bought Good Day coffee products with a sample size of 110 people. Data collection through questionnaires in the form of google forms. The analysis technique uses path analysis and sobel test with the help of the SPSS for windows program. The results showed that the credibility of celebrity endorsers has a positive and significant effect on brand image. Celebrity endorser credibility and brand image have a positive and significant effect on purchase intention. Brand image significantly mediates the effect of celebrity endorser credibility on purchase intention.